IRRI-DG’s visit of mechanized-DSR clusters and interaction with the stakeholders - Kumar, Virender; Kumar, Ashok; Mohapatra, Bidhan (International Rice Research Institute, 2024)
A Quick Overview Dr. Yvonne Pinto, Director General of the International Rice Research Institute (IRRI), accompanied by Dr. Virender Kumar, Interim Research Director and Head of the Sustainable Impact Department, Research Leader for Climate-Resilient Farming Systems, and DSR-Odisha Project Lead, Dr. Sudhanshu Singh, Director of the IRRI South Asia Regional Centre (ISARC), and Dr. Ashok Kumar, Sr. Associate Scientist-II Program Coordinator, IRRI visited three mechanized direct seeded rice (mech-DSR) clusters viz. Danpur, Ramachandrapur, and Sujanapur villages in Delang block of Puri district in Odisha, India, on December 3, 2024. She interacted with demonstration farmers at the spot itself. At the Danpur cluster, in addition to the field visits and interactions with the concerned farmer Mr. Bikram Parida, Dr. Pinto visited stalls showcasing essential farm machinery including multi-crop planters fitted with inclined plate seed metering system for mech-DSR and other crops in sequence, power weeders, and sprayers, suitable herbicides, and IRRI-GoO-DSR-Odisha project publications and standees. Dr. Pinto also interacted with a wide range of stakeholders, including farmers, service providers, and strategic partners. Over 100 participants including 23 females from across 8- districts of Odisha (Bargarh, Bhadrak, Ganjam, Mayurbhanj, Puri, Khordha and Cuttack) attended the event, representing diverse groups such as farmers, service providers, agriculture officials, KVK scientist, NGO partners, private companies, project staff, and the media. This way she could get a quick feedback and updates on the project's interventions, impacts and insights. Two significant aspects of the event were: 1) an in-depth meeting with stakeholders, where Dr. Pinto engaged with farmers and strategic partners to discuss the challenges, benefits, and future opportunities related to mech-DSR based systems in Odisha, and 2) the stakeholders' expectations and keen interest in hearing Dr. Pinto’s vision for agricultural development, particularly regarding the mechanized DSR-based system in Odisha.